Commodification of forestlands and assault on indigenous knowledge within forest-dependent communities of Cross River State, Nigeria. Issue 2 (4th May 2019) - Odok, Godwin Etta
Abstract : The basic component of any society's knowledge system is undoubtedly its indigenous knowledge. This consists of skills, experiences and insights which the people apply to maintain and improve their lives. Indigenous patterns of behaviour are well known for not only being relevant for preserving local forest resources but also for enriching livelihood systems. Adopting participatory rural appraisal research methods consisting of transects, trend analyses, seasonal calendars, institutional analyses and direct observations, this paper discusses how increased privatisation of forestlands and resources within forest-dependent communities of Cross River, Nigeria is evolving into well-developed alienating structures of neoliberal markets, thereby incapacitating local populations in adapting to environmental changes and resulting stressors of extreme events. This issue is also complicated by their cultural ability to tackle challenges of external adaptation and internal integration that confront them. Hence, actions and policies of forest conservation within forest-dependent communities of Cross River need to be more directed at promoting indigenous knowledge systems that brace common meaning for forests. Indigenous educational systems should also be strengthened in ways that help community people begin to think historically about alternative outcomes, and how they are agents and victims of history and their forestlands and resources are no longer for the public good.